INFECTION CONTROL CIRCLE OF SAFETY - McKay, Marcy; Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2006)
This article is based on a presentation given by the authors at the 42nd Congress of the Association for Perioperative Practice (AfPP), October 2006, in the United Kingdom. The conference theme was Circles of Influence and the Congress also hosted an International Federation of Perioperative Nurses (IFPN) Study Day featuring a safety theme. This article contains a brief review of the influence of infection control practices on perioperative practice and surgical outcome. It reviews the Principles of Asepsis and accepted infection control practices. Patient safety is more closely monitored today than ever before – not only by hospitals but also by consumers, health care reformers, governments and patients. The Canadian Institute for Health Information, (CIHI) shows one in nine Canadian adults acquire a hospital infection and that one in nine receives an incorrect medication or medication dosage. Our rates of patient deaths following an adverse event are higher than the combined death rates for Canadians involved in motor vehicle accidents, suffering from breast cancer, and HIV Positive.7 Each perioperative practitioner must use all available resources to assist in the safety of everyone involved in surgical interventions.